Marcas no corpo - Voss, Nadja da Silva (2013)
Essay about the creational process of the book Marcas no Corpo, from my authorship. We think in pictures. All languages are formed as images in our mind, which makes the narrative writing a junction of verbal and visual languages . With that, I believe in a semi-verbal semiosis, from a reading with the body, amending this same body and thoughts, and, reinforced by the hybridity that I propose in the book, ie, the expansion of synesthesia by blurring of boundaries, enhances reading by the consciousness of the body. I also believe that this semi-verbal semiosis is conscious to the author, and thus the multiple semiosis usage, now increasingly common, make possible a hypertextuality of high interactivity and motion, where the limits author-reader dilute, making room for an complete performative experience. With the book, I sought interactive aspects between text-image, and especially between book-reader; and all these interactive processes arise from scripture itself. Is to the manuscript I turn to determinate the plasticity of a page. Are the drawings, graphic signals and inter-texts of the manuscript that dictate the fi nal form of the book, so that more of the original content of the primary image is maintained.